(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research deals with the language of poetic creativity that preoccupied Nizar Qabbani in a remarkable way, in his last poem “Jasmine Alphabet”, prescient in the final stage of his life, including the variety of elements that formed the basis of his poems, during the five decades of his experience, and with a variety of conditions that have been changed, through that long journey, as it began with the delinquency of this language towards degradation and perish, as a continuation of the deterioration of his health and the prediction of his death, then he tried to restore his previous language that brought him to the peak of his glory in the poetic world. He then ended up dreaming of creating a new language, better in satisfying his infinite aspirations. Although he realized that his remaining days are not sufficient to achieve this end which requires another age.